1992
DOI: 10.1139/l92-032
|View full text |Cite
|
Sign up to set email alerts
|

Bridge dynamics and dynamic amplification factors — a review of analytical and experimental findings

Abstract: The dynamic amplification factor (DAF) is an important parameter in the design of highway bridges and yet no worldwide consensus has been reached so far as to its value. Some disagreement exists between provisions of various national bridge codes. This is because the DAF depends, in addition to the maximum span or the natural frequency, on many other parameters that are difficult to take into account with reasonable accuracy. Vehicle speed, weight, and dynamic characteristics, the state of the structure, roadw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(73 citation statements)
references
References 0 publications
1
67
0
5
Order By: Relevance
“…Consequently, all modern measuring technologies for bridge structures can be divided into three groups. The first group includes the use of radar systems of millimeter and optical ranges of electromagnetic waves [10][11][12][13][14][15] for estimation of deformations and deflections of bridge elements, including stay-cables which support the buildings. For this purpose, in particular, phase interferometers with a high-resolution range are used.…”
Section: Special Issue On Advancement In Engineering Technologymentioning
confidence: 99%
“…Consequently, all modern measuring technologies for bridge structures can be divided into three groups. The first group includes the use of radar systems of millimeter and optical ranges of electromagnetic waves [10][11][12][13][14][15] for estimation of deformations and deflections of bridge elements, including stay-cables which support the buildings. For this purpose, in particular, phase interferometers with a high-resolution range are used.…”
Section: Special Issue On Advancement In Engineering Technologymentioning
confidence: 99%
“…In 1992, P. Paultre et al [1,2,3] carried out a review of all the analytical and experimental studies that had previously been carried out. At the time, dynamic amplification factors were estimated on the basis of just one parameter, namely the span or the principal vibration frequency.…”
Section: Research Into Dynamic Amplification Factorsmentioning
confidence: 99%
“…First of all, in order to determine the upper limit, let us assume that it is an undamped structure. In this case, the dynamic response of the structure to load q(x) applied instantaneously in t=0 is (1) and the static response of the structure to that same action is…”
Section: Upper Limit Of Dynamic Amplification Factors Related To Deflmentioning
confidence: 99%
“…Kim, Lynch, Lee & Lee, 2011;Lin & Yang, 2005;Mazurek & DeWolf, 1990;Paultre, Proulx & Talbot, 1995;Yin & Tang, 2011) . A review by Paultre, Chaalal and Proulx (1992) showed that the mechanical properties of the vehicle affects the dynamic response of the bridge, when the two interact from the roughness of the bridge surface. However, these excitation frequencies lie between 2-5Hz for the bounce of the vehicle's body, and would have limited effect on bridge modes with lower frequencies.…”
Section: Introductionmentioning
confidence: 99%